Smoking has a dose-dependent effect on the incidence of preoperative opioid consumption in female geriatric patients with spine disease. (November 2020) - Christian, Zachary K.; Youssef, Carl A.; Aoun, Salah G.; Afuwape, Olusoji; Barrie, Umaru; Johnson, Zachary D.; El Ahmadieh, Tarek Y; Hall, Kristen; Peinado Reyes, Valery; Wingfield, Sarah A.; Bagley, Carlos A.
Highlights: Tobacco use appears to affect preoperative narcotic intake in spine patients. Opioid intake seems to increase with the number of pack years, independently of current smoker status. Female patients appear to be more affected than male patients when it comes to narcotic intake and smoking. Abstract: Tobacco use and narcotic medication have been associated with worse functional outcomes after surgery. Our goal was to investigate potential associations between smoking and preoperative opioid consumption in a geriatric population undergoing spine surgery, and their impact on postoperative outcomes. The records of 536 consecutive patients aged more than 65 years who underwent elective spinal surgery between November 2014 and August 2017 at a single institution were reviewed. Primary outcomes included rates of preoperative opioid consumption and postoperative hospital length of stay and complications. Males were more likely to be smokers than females (p < 0.001), whereas females were more likely to take opioid analgesics preoperatively (p = 0.022). Women with a history of smoking were more likely to have increased preoperative opioid consumption compared to those with no history of smoking (63.64% vs. 42.04%; p < 0.001). Such a relationship was not found in men. Subgroups analysis of female patients with a history of tobacco use comparing current and former smoker status showed that both groups exhibited increased preoperative opioid consumption compared to patients who never smoked (88.89% vs 42.04%; p < 0.001 for current users; 59.42% vs 42.04% for former users; p = 0.008). There was also a dose-depended relationship between smoking and increased preoperative opioid consumption. Geriatric female spine patients with a history of smoking have a higher incidence of preoperative opioid consumption. Opioid intake appears to increase with the number of pack-years, both in patients with a history of smoking and in those who currently smoke.